2022
DOI: 10.1088/1742-6596/2187/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Research and Analysis on Cavitation of Different Structures of Cone Valve Ports in Pure Water

Abstract: In order to study the cavitation problem of the pure water medium hydraulic poppet valve, a three-dimensional model of the poppet control valve under a rated pressure of 31.5MPa was established with the help of Soildworks software, and the poppet valve port model was simplified into a two-dimensional symmetrical model with AutoCAD software. Based on the FLUENT software, the liquid-gas two-phase flow simulation of the cavitation phenomenon in the flow field of the poppet valve is carried out, and the cavitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Qin et al [5] experimentally researched the vibration and noise of throttle valves with different structures and pointed out that multi-stage throttle structures can effectively reduce throttle valve noise. Zhou et al [6] summarized the cavitation distribution law of the cone valve with different structures at different openings. Li et al [7] found that the shape and structural parameters of the flow channel inside the valve have a certain functional correlation with pressure drop and Mach number through experiments and numerical analysis, and the research results provide a reference for noise control of throttle valves.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al [5] experimentally researched the vibration and noise of throttle valves with different structures and pointed out that multi-stage throttle structures can effectively reduce throttle valve noise. Zhou et al [6] summarized the cavitation distribution law of the cone valve with different structures at different openings. Li et al [7] found that the shape and structural parameters of the flow channel inside the valve have a certain functional correlation with pressure drop and Mach number through experiments and numerical analysis, and the research results provide a reference for noise control of throttle valves.…”
Section: Introductionmentioning
confidence: 99%